Antihypertensive responses elicited by central moxonidine in rats: Possible role of nitric oxide - Moreira, Thiago Santos; Thomaz Takakura, Ana Carolina; Sato, Monica Akemi; Menani, José Vanderlei [UNESP]; Colombari, Eduardo [UNESP] (Lippincott Williams & Wilkins, 2006)
In the present study, we investigated the effects of pretreatment with N-G-nitro-L-arginine methyl ester (L-NAME) (nitric oxide synthase inhibitor) injected intravenously (IV) on the hypotension, bradycardia, and vasodilation produced by moxonidine (alpha(2)-adrenergic/imidazoline receptor agonist) injected into the fourth brain ventricle (4th V) in rats submitted to acute hypertension that results from baroreflex blockade by bilateral injections of kynurenic acid (kyn, glutamatergic receptor antagonist) into the nucleus of the solitary tract (NTS) or in normotensive rats. Male Wistar rats (n = 5 to 7/group) anesthetized with IV urethane (1.0 g kg(-1) of body weight) and a-chloralose (60mg kg(-1) of body weight) were used. Bilateral injections of kyn (2.7 nmol 100 nL(-1)) into the NTS increased baseline mean arterial pressure (148 +/- 11 mm Hg, vs. control: 102 +/- 4mm Hg) and baseline heart rate (417 +/- 11 bpm, vs. control: 379 +/- 6 bpm). Moxonidine (20 nmol mu L-1) into the 4th V reduced mean arterial pressure and heart rate to similar levels in rats treated with kyn into the NTS (68 +/- 9 mm Hg and 359 +/- 7 bpm) or in control normotensive rats (66 +/- 7 mm Hg and 362 +/- 8 bpm, respectively). The pretreatment with L-NAME (2 5 mu mol kg-1, IV) attenuated the hypotension produced by moxonidine into the 4th V in rats treated with kyn (104 +/- 6 mm Hg) or in normotensive rats (95 +/- 8 mm Hg), without changing bradycardia. Moxonidine into the 4th V also reduced renal, mesenteric, and hindquarter vascular resistances in rats treated or not with kyn into the NTS and the pretreatment with L-NAME IV reduced these effects of moxonidine. Therefore, these data indicate that nitric oxide mechanisms are involved in hypotension and mesenteric, renal, and hindquarter vasodilation induced by central moxonidine in normotensive and in acute hypertensive rats.
Keywords: sympathetic; alpha(2)-adrenergic/imidazoline receptor; blood pressure; hypertension; L-NAME